Penerapan Model Pembelajaran Group Investigation pada Mata Pelajaran Sejarah dalam Meningkatkan Hasil Belajar Siswa - Zainimal Said (Tarikhuna: Journal of History and History Education, 2023)
This study was motivated by the problem of the lack of use of learning models in the teaching and learning process, as well as the lack of active students to the learning process in the History class X IPS SMA Negeri 12 Padang. This study aims to determine whether the application of the Group Investigation (GI) learning model can improve the learning outcomes of students in class X IPS SMA Negeri 12 Padang. This type of research is quantitative research with an experimental approach. The sample in this study were X IPS class students consisting of 35 people from the control class and 35 people from the experimental class. The instrument used for data collection is a test question (pretest and posttest). The results of (pretest and posttest) were analyzed using SPSS 25. From the research results obtained pretest data in the control class obtained an average of 60.71 with the highest score of 80 percentage level 17.6%, while the value of the experimental class obtained an average of 64.71 with the highest score of 90 percentage level 8.6%. And posttest data in the control class obtained an average of 73.00 with the highest score of 95 percentage level 2.9%, while the value of the experimental class obtained an average of 82.29 with the highest score of 100 percentage level 5.7%. The results of this study indicate that the application of the Group Investigation (GI) Learning Model can be one way or solution that can be used to improve the learning outcomes of History students in class X IPS SMA Negeri 12 Padang.